Study on the adsorption of phosphorus from phosphorus-containing wastewater using composite mineral-based adsorbent materials derived from phosphate tailing - Yihuai Su; Hongwei Wei; Ting Xu; Zeming Shi; Chengwen Wang (Minerals Engineering, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Interplay of microplastics and bioturbation on atrazine dynamics in aquaculture sediments - Bokang Liu; Yifan Jiang; Rongrong Zhang; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Source apportionment and probabilistic health risk assessment of soil heavy metals in a high-background carbonate region of Southwest China - Ge Jin; Zhaoyu Zhou; Zeming Shi; Yafeng Zhang; Huan Deng; Zhangliang Shi (Environmental Geochemistry and Health, 2026)

Non-additive effects of microplastics, atrazine, and sulfamethoxazole co-exposure on Penaeus vannamei health and environmental risks - Yinan Wang; Qiangqiang Shi; Weijia Gan; Feng Xu; Hao Liu; Liuquan Zhang; Rongrong Zhang; Jiong Chen; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Battling PFAS: Microbial frontlines and removal mechanisms in constructed wetlands - Yaoxuan Cheng; Jiacheng Shang; Xuanrui Liu; Zeming Shi; Xinyue Zhao; Lixin Li (Journal of Environmental Chemical Engineering, 2026)

The silent drift of PAHs in the East China Sea: Sources, ecological risks, and remediation - Liberty Chidewe; Rongrong Zhang; Lord Famiyeh; Kalim Ullah; Qunying Lu; Zeming Zhang; Xizhi Shi (Regional Studies in Marine Science, 2026)

Influence of DOM on Cd speciation during soil weathering in Permian strata: A case study in Xingwen County, Southern Sichuan Province, China - Ge Jin; Zeming Shi; Huan Deng; Tianliang Zheng; Yafeng Zhang; Jixiang Xie; Zhangliang Shi; Yinghai Zhu; Na Zhang; Chengjie Zou (Journal of Hazardous Materials, 2026)

Microalgae in multipollutant synergistic removal: mechanisms, regulatory networks, and cross-scale integration - Chunlai Song; Zeming Shi; Lixin Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Geochemical signature and genesis of heavy metals in soils and sediments from a typical pyrite mining area in Southwestern China - Kai Zhao; Zeming Shi; Yinghai Zhu; Yixin Li; Qi Liu; Qiuyu Huang; Xiaohan Liu (Environmental Geochemistry and Health, 2026)

Critical control points in Penaeus vannamei aquaculture: Dynamic tracking and comprehensive risk assessment of antibiotics - Feng Xu; Chenxue Yang; Hua Liu; Hao Liu; Mingze Chen; Yinliang Wu; Xizhi Shi; Zeming Zhang; Rongrong Zhang (Journal of Hazardous Materials, 2025)

Occurrence and ecological risks of organochlorine pesticides and polychlorinated biphenyls in a semi-enclosed urban watershed - Liberty Chidewe; Rongrong Zhang; Xizhi Shi; Zeming Zhang (Frontiers in Marine Science, 2025)
Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) are pollutants of global concern due to their toxicity, bioaccumulation, and long-term ecological consequences in marine ecosystems. Their presence and associated hazards were investigated in the water–sediment system of the Xiangshan Harbour Watershed, a zone influenced by both industrial and agricultural activities. Samples were obtained from 19 key locations during autumn (October 2020) and summer (July 2021). OCP concentrations ranged from 0.03–231.52 ng/L in water and 0.28–804.27 μg/kg in sediment, while PCBs ranged from 0.01–7.35 ng/L in water and 0.35–3.77 μg/kg in sediment. The lower section of the XianXiang River (XX-DOWN) was the hotspot for OCPs, and the Huangduan Harbor lower section (HDG-DOWN) was the hotspot for PCBs. Temperature and salinity were positively correlated with pollutant concentrations. Source identification using diagnostic ratios indicated OCPs mainly originated from lindane and technical DDT, while PCA–MLR analysis showed PCBs were sourced from e-waste (15.3%), thermoplastics (57.1%), and pigments (27.6%). Risk quotient (RQ) analysis revealed ecological risks from hexachlorobenzene, PCB 138, and DDT metabolites. Total non-carcinogenic hazard quotient (TnHQ) values remained below 1 for all assessed age groups—infants, children, teens, and adults—indicating low risks. Continuous surveillance along with targeted pollution control strategies in the watershed are encouraged.

Causes and influencing mechanisms of differences in phosphorus occurrence forms in sediments of different types of urban lakes - Yinghai Zhu; Zeming Shi; Qian Li; Chengjie Zou; Na Zhang; Xinyu Wang; Kai Zhao (Science of The Total Environment, 2025)

Co-exposure to enrofloxacin and atrazine enhances the hepatotoxicity in Larimichthys crocea by targeting the hypothalamic–pituitary–thyroid and gut–liver axes - Yinan Wang; Chenxue Yang; Qiangqiang Shi; Liuquan Zhang; Hao Liu; Jinjie You; Rongrong Zhang; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2025)

Effects of elevated CO2 concentration on Se accumulation and associated rhizobacterial community in Cardamine hupingshanensis - Huawei Zang; Wenyao Shi; Minyi Kau; Jiayuan Li; Jinxing Li; Wanying Zhang; Zeming Zhou; Bowen Sun; Linxi Yuan; Renbin Zhu (Plant and Soil, 2025)

Geographical impact on the distribution of polycyclic aromatic hydrocarbons (PAHs) in hilly terrain topsoil: A case study at Chongqing, SW, China - Jianghai Liao; Xinyu Wang; Hangjia Wang; Mingcai Hou; Sizhuo Zhou; Zeming Shi; Yuxiang Zhan; Shijun Ni; Ruilin Wang (Journal of Hazardous Materials, 2025)

Accumulation patterns and chronic toxic effects of triphenyl phosphine in Mytilus coruscus - Ningbo Wang; Yinan Wang; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

Unraveling the pharmaceutical footprint and risks of combining different aquaculture modes and tailwater treatment systems - Feng Xu; Yangcai Wang; Qiangqiang Shi; Yinliang Wu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

Combined ecotoxicity of polystyrene microplastics and Di-(2-ethylhexyl) phthalate increase exposure risks to Mytilus coruscus based on the bioaccumulation, oxidative stress, metabolic profiles, and nutritional interferences - Yinan Wang; Qiangqiang Shi; Menglan Zhang; Lingyan Xu; Qiang Wei; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Ions release stages of Cu-Pb-Zn mine tailings waste: A column leaching simulation - Lei Xu; Liang Tang; Zeming Shi; Jingsong Yang; Kunhao Shi; Haili Zhang; Yuting Yuan (Ore and Energy Resource Geology, 2024)

Accumulation and growth toxicity mechanisms of fluxapyroxad revealed by physiological, hepatopancreas transcriptome, and gut microbiome analysis in Pacific white shrimp (Litopenaeus vannamei) - Ningbo Wang; Rongrong Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Revisiting Neoproterozoic tectono-magmatic evolution of the northern margin of the Yangtze Block, South China - Peng Wu; Yuan-Bao Wu; Shao-Bing Zhang; Yong-Fei Zheng; Long Li; Ying Gao; Hao Song; Zhengqi Xu; Zeming Shi (Earth-Science Reviews, 2024)

Unveiling the hidden risks: Pesticide residues in aquaculture systems - Weijia Gan; Rongrong Zhang; Zhi Cao; Hao Liu; Wentao Fan; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Effects of coal-fired power plants on soil microbial diversity and community structures - Bowen Sun; Renbin Zhu; Yu Shi; Wanying Zhang; Zeming Zhou; Dawei Ma; Runfang Wang; Haitao Dai; Chenshuai Che (Journal of Environmental Sciences, 2024)

Comparative antioxidant and metabolomic analysis for the identification of differential response of mussel (Mytilus coruscus) to four succinate dehydrogenase inhibitor fungicides - Ningbo Wang; Zeming Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Hua Liu; Xizhi Shi (Environmental Science and Pollution Research, 2024)

Accumulation and elimination properties and comparative toxicity of fluxapyroxad in juvenile and adult large yellow croaker (Larimichthys crocea) - Ningbo Wang; Yinan Wang; Aili Sun; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Spatial-temporal evolution of ecological risks in a typical urban lake in Southwestern China - Yinghai Zhu; Zeming Shi; Xinyu Wang; Chengjie Zou; Na Zhang; Peijia Zheng; Jianming Wang; Yu Wang (Journal of Cleaner Production, 2024)

Origin, formation, and transformation of different forms of silica in Xuanwei Formation coal, China, and its’ emerging environmental problem - Zailin Chen; Zeming Shi; Shijun Ni; Bangzheng Ren; Junchun Hu (Environmental Science and Pollution Research, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

Simultaneous determination and dietary intake risk assessment of 60 herbicide residues in aquatic products - Xinru Yu; Feng Xu; Rongrong Zhang; Hua Liu; Aili Sun; Liuquan Zhang; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2023)

Environmental profile, potential sources, and ecological risk of polycyclic aromatic hydrocarbons in a typical coastal bay and outer bay area - Yuyao Wu; Zeming Zhang; Wei Huang; Hua Liu; Rongrong Zhang; Haifeng Jiao; Aili Sun; Jiong Chen; Xizhi Shi (Environmental Science and Pollution Research, 2023)

Uranium sorption onto mullite: Characteristics of isotherms, kinetics and thermodynamics - Liao Rong; Shi Zeming; Hou Yun; Zhang Kailiang; Zhang Junji; Wang Xinyu; Cheng Ke; Yang Lvhang (Journal of Earth System Science, 2019)

Are spatial distributions of major elements in soil influenced by human landscapes? - Huan Yu; Zhengwei He; Zeming Shi; Bo Kong (Acta Geochimica, 2018)

Mechanism of post-seismic floods after the Wenchuan earthquake in the upper Minjiang River, China - Ding Hairong; Li Yong; Shao Chongjian; Lauvence Svirchev; Xu Qiang; Yan Zhaokun; Yan Liang; Ni Shijun; Shi Zeming (Journal of Earth System Science, 2017)

Characteristics, Sources and Health Risk Assessment of Trace Metals in PM10 in Panzhihua, China - Xin Cheng; Yi Huang; Zhijie Long; Shijun Ni; Zeming Shi; Chengjiang Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)